(untitled) (Research, Society and Development, 2020)
Objective: to analyze samples of vegetables Lactuca sativa (lettuce), Allium schoenoprasum (chives), Coriandrum sativum (coriander) and Eruca sativa (arugula) sold in supermarkets and open markets in the municipality of Piripiri- Piaui, as well as to evaluate the effectiveness of the method of washing food using 2% sodium hypochlorite. Methodology: Parasitological analysis was carried out at the Parasitology Laboratory of Cristo Faculdade do Piaui, using the spontaneous sedimentation method of Hoffman, Pons and Janer adapted for parasitological evaluation in food. Results: Of the 96 samples analyzed, 93.75% demonstrated the presence of some parasitic structure. And the effectiveness of food hygiene using 2% sodium hypochlorite was seen. Conclusion: it is necessary to carry out health education practices for producers, traders and consumers regarding health risks.